Lecturer’s Perceptions on the English Writing Competency in a Public University: A Focus Group Discussion - Sulaiman, Fazillah; Bakar, Erda Wati (Advances in Social Sciences Research Journal, 2024)
This study has been conducted to find out the lecturers’ perceptions of the students’ writing competency in a public university. The objective of the study is to explore the definition of a good piece of writing according to the lecturers and to know the strength and weakness of the students. In this public university, in all Faculties, major assignments are completed through writing, therefore students have to express themselves clearly and efficiently through their writing. This is a qualitative study using Focus Group Discussion with a total number of eight lecturers representing four main Faculties at the main campus. The Faculties are Laws, Economics and Management Sciences, Engineering and Human Sciences. Based on the Focus Group Discussion, the lecturers considered ideas and content, organisation, grammar and spelling as the three top important elements in writing. The lecturers considered the students as confident writers or ‘shameless’ writers which they believed is a significant element of being a good writer. The students have difficulties generating ideas. Thus, they will not be able to expand their writing further for their written assignments or projects. The lecturers added that lack of ideas is related to reading as well. Students who read more will be a better writer.